Improving FTO/ZnO/In2S3/CuInS2/Mo solar cell efficiency by optimizing thickness and carrier concentrations of ZnO, In2S3 and CuInS2 thin films using Silvaco-Atlas Software - Agoundedemba, Maklewa; Baneto, Mazabalo; Nyenge, Raphael; Musila, Nicholas; Toure, Kicoun Jean-Yves N'Zi (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Optimization of optical and electrical properties of active semiconducting layers is required to enhance thin film solar cells' efficiency and consequently became the cornerstone for sustainable energy production. Computational studies are one of the ways forward to optimize solar cells’ characteristics. In this study, Silvaco-Atlas, a powerful software that excels in both 2D and 3D electrical simulations of semiconductors has been used for the simulation in order to investigate the solar cell properties. The architecture of the solar cell simulated was FTO/ZnO/In2S3/CuInS2/Mo. This study aims to optimize solar cell efficiency by optimizing film thicknesses and carrier concentrations via simulation. The designed solar cell was exposed to the presence of a sun spectrum of AM1.5 from a 1kW/m2 incident power density at 300K. The thickness values of the window (ZnO), absorber (CuInS2) and buffer (In2S3) layers were varied to record a solar cell's optimum thickness. The resulting FTO/ZnO/In2S3/CuInS2/Mo solar cell formed by simulation is presented. The best efficiency and fill factor of the solar cell simulated were found to be 41.67% and 89.19%, respectively. The recorded values of current density and the open circuit voltage of the cell were 40.33mA/cm2 and 1.15 V, respectively. Additionally, the maximum power of the simulated solar cell device was 41.68 mW. Optimization results revealed that the most efficient cell found was made up of a window layer with a thickness of 0.03μm, an absorber layer with a thickness of 6.0μm and a buffer layer with a thickness of 0.2μm. The optimized carrier concentration of ZnO, In2S3 and CuInS2 was respectively 1e21 cm-3, 1e20 cm-3, 3e18 cm-3 and the optimized Al-doped ZnO value was 1e25 cm-3. The Absorption spectra indicated that the solar cell's peak absorption occurs between 350 nm and 1250 nm and presented a good external quantum efficiency (EQE) of around 84.52% to 92.83% which indicates good efficiency in the visible domain. This performance is attributed to the transparency of FTO, ZnO and good absorption of In2S3 and CuInS2 thin films.